Protozoários flagelados heterotróficos e a cadeia alimentar planctônica em uma lagoa rasa da planície de inundação do alto rio Paraná. - Silva, Bianca Trevizan Segovia da (2011)
Considering the growing interest in organisms belonging to the microbial food chain, the temporal and vertical changes in the density of heterotrophic flagellates was investigated, defining which mechanisms control their density, as well as enlighten the interactions between them and the other plankton components, in a shallow lake at the Paraná River floodplain. The relative importance of bottom-up and top-down in controlling the density of the heterotrophic flagellates community was quantified and assessed in this study. Samples were taken monthly, between March 2007 and February 2008, in three distinct sampling sites in Guaraná Lake (State of Mato Grosso do Sul, Brasil) at three depths of each one (surface, middle and bottom). The research was structured primarily focusing on the heterotrophic flagellates, resulting in the analysis of the effects of bottom-up and top-down on heterotrophic flagellates in different layers of the water column in a shallow floodplain lake, in which we observed a gradual decoupling of bacteria-flagellates, from the surface to the bottom of the lake, due to the presence of a high density of cladocerans in the deeper layer, which exert a high predation pressure on the flagellates thus interfering on the previous relation. Afterwards, the importance of the microbes in the planktonic food web of the shallow Paraná River floodplain lake was highlighted and it was noticed that the planktonic food chains dynamics were strongly influenced by the hydrological regime of this lake, as the flood favored the interactions among the components of the microbial food chain over the relations of these with the components of the traditional grazing food chain.